Exploring the Readability Level of Indian Companies’ Management Discussion and Analysis Reports (International Journal of Food and Nutritional Sciences, 2022)
This research explores the readability of Management Discussion and Analysis (MD&A) Reports of Nifty 50 companies. Regulations necessitate that publicly listed companies include MD&A reports in their annual disclosures. The sample comprises the top 50 companies listed on the National Stock Exchange (NSE). The Flesch readability method is employed to assess the comprehensibility of MD&A content, a method widely used in prior research. The findings indicate that MD&A reports from Indian listed companies exhibit challenging readability and can be understood by postgraduate students. These findings offer valuable insights for companies and regulators to enhance the clarity and accessibility of their MD&A Reports, as required by the Securities and Exchange Board of India (SEBI). This study is a novel addition to the literature, as prior investigations have not delved into the readability aspect of MD&A reports in the Indian scenario.